Expression Profiles of MYC Protein and MYC Gene Rearrangement in Lymphomas. (March 2015) - Chisholm, Karen M.; Bangs, Charles D.; Bacchi, Carlos E.; Kirsch, Hernan Molina-; Cherry, Athena; Natkunam, Yasodha
<x xml:space="preserve">Abstract</x> MYC translocations are a defining feature of Burkitt lymphoma and a group of diffuse large B-cell lymphoma (DLBCL) with inferior outcome. However, the clinical relevance of MYC gene rearrangement and its relationship with MYC protein expression has not been well characterized in lymphomas. Tissue microarrays containing 1214 lymphomas were successfully evaluated by immunohistochemistry using anti-MYC clone Y69 and a dual-color break-apart fluorescence in situ hybridization probe to detect MYC gene rearrangements. Aggressive B-cell lymphomas including Burkitt lymphoma and DLBCL showed the highest level of MYC protein staining defined as staining in >50% of lymphoma cells. A significant proportion of plasmablastic, B-lymphoblastic and T-lymphoblastic, and extranodal NK/T-cell lymphomas also showed staining in >50% of cells, whereas only occasional plasma cell myeloma, mantle cell lymphoma, and classical Hodgkin lymphoma showed a high level of staining. Small B-cell lymphomas, when positive, showed MYC protein in <50% of cells. In aggressive B-cell lymphomas, MYC rearrangement and MYC immunohistochemistry showed a high concordance rate; however, some DLBCL and all T-cell and NK-cell lymphomas with MYC protein expression lacked MYC gene rearrangements. Our results provide a baseline for MYC protein expression in lymphomas and indicate that its expression is not specific to lymphoma subtypes, cell lineage, or expected clinical behavior and is highly variable. In addition, MYC protein expression is not necessarily correlated with MYC gene rearrangements and suggests the need for caution in the interpretation of MYC immunohistochemistry in the differential diagnosis of lymphomas.